National Vigilance Against Threats Towards Democratic Consolidation in Indonesia - Wingarta, I Putu Sastra (Lembaga Ketahanan Nasional Republik Indonesia, 2024)
Purpose: This study examines the role of national vigilance in addressing threats and ensuring the successful consolidation of democracy in Indonesia, focusing on internal and external challenges. Study Design/Methodology/Approach: A qualitative descriptive approach is applied, integrating theoretical frameworks, geopolitical analysis, and data from the National Resilience Laboratory (Labkurtannas). The study analyses the synergy of democratic elements, including political institutions, civil society, and national values, supported by programmes such as the National Values Strengthening Programme by Lemhannas RI. Findings: The study indicates that national vigilance is indispensable in countering asymmetric threats such as radicalism, ideological infiltration, and social polarisation. While challenges remain, including weak political ethics and systemic corruption, leveraging democratic elements and strengthening national values can enhance resilience. Programmes promoting Bhinneka Tunggal Ika significantly contribute to fostering nationalism and addressing modern challenges. The research also highlights the need for integrated strategies to anticipate digital-era threats. Originality/Value: This study underscores the strategic role of national vigilance as a unifying framework for consolidating democracy in Indonesia. It provides actionable recommendations for policymakers and identifies areas for future research on national resilience in the context of digital and asymmetric threats.